Molecular insights into the inhibition of angiotensin-converting enzyme 1 by hemopressin peptides - Priya Antony; Bincy Baby; Aaesha Rahma; Shamaa Abdul Samad; Yusra Al Dhaheri; Ranjit Vijayan (Scientific Reports)
Abstract Inhibiting angiotensin-converting enzyme 1 (ACE1) is a key strategy for managing hypertension as it prevents the formation of angiotensin II, a potent vasoconstrictor. Given the adverse effects associated with synthetic inhibitors, there is an increasing focus on exploring natural bioactive peptides as potential ACE1 inhibitors. Hemopressins (Hp) are peptides derived from hemoglobin. The present study investigated the ACE1 inhibitory activity of two Hp variants, Hp bearing phenylalaine (Hp-F) and Hp bearing leucine (Hp-L), using a combination of in vitro and in silico methodologies. In enzyme inhibition assays, Hp-L variants exhibited better inhibition when compared to Hp-F variants. Furthermore, in molecular docking and molecular dynamics simulations, Hp-L variants displayed favorable binding characteristics, in terms of binding energy and interactions, supporting their potential to be effective ACE1 inhibitors. The peptides were observed to interact with key residues involved in binding widely used ACE1 inhibitors. Notably, peptide RVD-Hp-L (RVDPVNFKLLSH) showed the lowest IC50 value, higher binding affinity and sustained interactions while binding to the catalytic site of ACE1. Finally, the substitution of phenylalanine with leucine in hemopressins significantly enhances their binding affinity and inhibitory potency.